Mencocokkan gambar sebagai aktivitas untuk menstimulasi fungsi kognitif lansia: A systematic review - Yulita, Refi; Rekawati, Etty (Talenta Publisher, 2023)
The older adults experience declining cognitive function, which characterized by the changing in brain structure and nervous tissue. This changing inevitably effects the daily activity of the older adults. Matching picture activity has the potential to stimulate brain. Hence, it can slow down the declining cognitive function of older adults. This study aimed to review the impact of matching picture activity on cognitive function among older adults. We conducted a systematic review on the articles published in the past 10 years. The articles were retrieved from Pubmed, ProQuest, Springerlink, dan Taylor & Francis database. A total of 10 articles met the inclusion criteria. All articles (100%) found that matching picture had a positive impact on the cognitive function of older adults. Further studies are required to examine the optimal matching picture intervention duration.